Duodenoscope-associated infection prevention: A call for evidence-based decision making - Ofstead, Cori L.; Buro, Brandy L.; Hopkins, Krystina M.; Eiland, John E.; Wetzler, Harry P.; Lichtenstein, David R. (Endoscopy International Open, 2020)
Background Recent outbreaks of duodenoscope-associated multidrug-resistant organisms (MDROs) have brought attention to the infection risk from procedures performed with duodenoscopes. Prior to these MDRO outbreaks, procedures with duodenoscopes were considered safe and low risk for exogenous infection transmission, provided they were performed in strict accordance with manufacturer instructions for use and multisociety reprocessing guidelines. The attention and efforts of the scientific community, regulatory agencies, and the device industry have deepened our understanding of factors responsible for suboptimal outcomes. These include instrument design, reprocessing practices, and surveillance strategies for detecting patient and instrument colonization. Various investigations have made it clear that current reprocessing methods fail to consistently deliver a pathogen-free instrument. The magnitude of infection transmission has been underreported due to several factors. These include the types of organisms responsible for infection, clinical signs presenting in sites distant from ERCP inoculation, and long latency from the time of acquisition to infection. Healthcare providers remain hampered by the ill-defined infectious risk innate to the current instrument design, contradictory information and guidance, and limited evidence-based interventions or reprocessing modifications that reduce risk. Therefore, the objectives of this narrative review included identifying outbreaks described in the peer-reviewed literature and comparing the findings with infections reported elsewhere. Search strategies included accessing peer-reviewed articles, governmental databases, abstracts for scientific conferences, and media reports describing outbreaks. This review summarizes current knowledge, highlights gaps in traditional sources of evidence, and explores opportunities to improve our understanding of actual risk and evidence-based approaches to mitigate risk.